Analisis Kajian Implementasi Sikap Luhur Interpersonal Terhadap Masyarakat - Fitriana Yasintha; Nabila Azrilia Syahra; Nur Azmi; Rawdia Tuzahara; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The position of morality in human life as social creatures has an important role and influence, this refers to the relationship between humans themselves and their environment, both directly and indirectly (online/cyberspace). In religion itself, morality is not just a polite attitude, but is the basis of human behavior. Morality is the basis for finding humans when God is the creator. Morals themselves in Islam are attitudes and habits that are developed, one of the ideas of which is not destructive but contrary to the cultural order and teachings that apply in nature. The aim of this research is to reveal how noble interpersonal attitudes are implemented in Pekanbaru 46 state elementary school students. The method used in this research is a qualitative method with a library research approach which makes books, magazines and journal articles related to the theme the main source in this research. The results of this research show that the implementation of noble interpersonal attitudes among students at SDN 46 Pekanbaru is quite good in terms of socializing with friends and neighbors.